Modified lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery
The modified lithium-rich manganese-based positive electrode material through multi-element doping and heterogeneous structure layer design solves the problem of unstable structure of existing materials, improves the cycle performance and capacity performance, and is suitable for lithium-ion batteries.
Patent Information
- Application Number
- CN202511093848.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-06
- Publication Date
- 2025-09-09
- Estimated Expiration
- 2045-08-06
AI Technical Summary
The existing lithium-rich manganese-based positive electrode materials are structurally unstable during the charge and discharge process, resulting in poor cycle performance, and the existing modification methods are difficult to balance industrialization and modification effects while ensuring performance.
By adopting a matrix material doped with multiple elements, combined with the design of heterogeneous structure layer and coating layer, a stable modified lithium-rich manganese-based positive electrode material is formed through single, double and triple sintering processes, including polycrystalline or single-crystal solid solution particles, spinel phase lithium manganate Li4Mn5O12 and a coating layer containing D compound.
The structural stability, cycle performance and rate performance of the material are significantly improved, and the capacity performance and electrochemical properties of the material are improved, making it suitable for large-scale production.
Smart Images

Figure CN120613388A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a modified lithium-rich manganese-based positive electrode material, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the widespread application of lithium-ion batteries in electric vehicles, energy storage systems, and other fields, the demand for cathode materials with high energy density, long cycle life, and high safety is growing. Lithium-rich manganese-based cathode materials have become a hot topic in lithium-ion battery cathode material research due to their high specific capacity (>250mAh / g), low cost, and environmental friendliness. Lithium-rich manganese-based cathode materials typically consist of a solid solution structure composed of layered Li2MnO3 and LiTMO2 (TM = Ni, Co, Mn, etc.). They have high theoretical capacity and operating voltage, but they still face many challenges in practical application.
[0003] During the charge and discharge process, lithium-rich manganese-based cathode materials experience irreversible migration of transition metal ions due to the involvement of anionic redox reactions, leading to structural instability. Furthermore, uneven lithium diffusion between the two phases leads to stress accumulation, causing atomic-level interlayer dislocations and particle fracture, severely impacting the material's long-term cycling stability and safety. Furthermore, lithium-rich manganese-based materials suffer from low initial coulombic efficiency and severe voltage decay, limiting their commercial application.
[0004] To solve the above problems, researchers have developed a variety of modification strategies. However, the modification methods in the existing technology still have some limitations. Although the liquid phase modification method has significant effects, the process is complicated and not convenient for industrialization; and although the solid phase modification method has low cost and simple control, it has the problem of poor diffusion ability of transition metal ions at the solid-solid interface, resulting in the inability to fully achieve effective doping. The elements are easily enriched on the surface of the material, affecting the modification effect. In addition, the structural design and element doping strategies of lithium-rich manganese-based materials in the existing technology have not yet completely solved the problem of structural stability of the material during long cycles, especially the irreversible phase change and capacity attenuation caused by anion redox reactions.
[0005] Therefore, under the premise of ensuring performance, how to balance industrialization and effective modification and develop a lithium-rich manganese-based positive electrode material with stable structure, excellent cycle performance and suitable for large-scale production is a technical problem that needs to be solved urgently. Summary of the Invention
[0006] The purpose of this application is to provide a modified lithium-rich manganese-based positive electrode material, a preparation method thereof, and a lithium-ion battery, aiming to solve the problems of structural instability and cycle attenuation of existing lithium-rich manganese-based positive electrode materials.
[0007] To achieve the above objectives, the present application provides a modified lithium-rich manganese-based positive electrode material, comprising: a base material, a heterogeneous structure layer and a coating layer; The matrix material is a polycrystalline or single-crystal solid solution particle, and its chemical formula is Li w Ni x Mn y M a N b L c O w+1-r Q r , where 1.2≤w≤1.4, 0.25≤x≤0.40, 0.50≤y≤0.70, 0.0005≤a≤0.002, 0.0001≤b≤0.002, 0.0001≤c≤0.004, x+y+a+b+c=1, 0≤r≤0.002; wherein M and L are independently selected from at least one of Nb, Ti, Mg, Co, W, La, Te and Ta, preferably, M is selected from at least one of Nb, Ti and Mg, L is selected from at least one of Co, W and La, more preferably, M and L are Nb and Co respectively; N is selected from at least one of Zn, Na, Cr, Zr and K, preferably, N is selected from at least one of Zn, Na and K, more preferably, N is Zn; Q is selected from at least one of F, Cl, S, B and P, preferably, Q is selected from at least one of F, Cl, S and P; The heterostructure layer contains spinel phase lithium manganate Li4Mn5O 12 ; The coating layer is a D-containing compound, which includes one or more of fluorides, oxides, sulfates, nitrates or phosphates of Al and / or La, and preferably includes one or more of fluorides, oxides, sulfates, nitrates or phosphates of Al.
[0008] In some embodiments, the internal porosity of the modified lithium-rich manganese-based positive electrode material is ≥15%, preferably 15% to 20%.
[0009] In some embodiments, the modified lithium-rich manganese-based cathode material has a secondary spherical morphology formed by accumulation of primary particles, and the average length of the primary particles is 150-200 nm.
[0010] In some embodiments, the average particle size D50 of the modified lithium-rich manganese-based positive electrode material is 3-10 μm.
[0011] The present application also provides a method for preparing the modified lithium-rich manganese-based positive electrode material, comprising: In an oxygen-containing atmosphere, Ni x Mn y(OH)2, a lithium source, a compound containing M, a compound containing N, and a compound containing L are mixed and sintered once to obtain a sintered product; The primary calcined product is subjected to secondary calcination under an inert atmosphere to obtain a secondary calcined product having a heterogeneous structure layer; The double-sintered product is mixed with an additive and sintered three times to obtain a modified lithium-rich manganese-based positive electrode material with a coating layer.
[0012] In some embodiments, at least one of the following conditions is met: A. The Ni x Mn y In (OH)2, 0.28≤x≤0.42, 0.58≤y≤0.72, x+y=1; B. the lithium source comprises at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate or lithium acetate; C. Ni x Mn y The molar ratio of (OH)2: the lithium source: (the compound containing M + the compound containing N + the compound containing L) is 0.997: (1.20-1.40): 0.003; D. The additive comprises at least one of aluminum fluoride, aluminum oxide, aluminum sulfate, aluminum nitrate, aluminum phosphate, lithium aluminum titanium phosphate, lanthanum oxide, and lithium aluminum zirconate; Preferably, the additive includes at least one of aluminum oxide, aluminum fluoride, aluminum phosphate, and lanthanum oxide; More preferably, the additive comprises aluminum fluoride; E. The amount of the additive added is 0.5%-1.5% of the mass of the di-sintered product.
[0013] In some embodiments, at least one of the following conditions is met: A. The primary sintering includes a first insulation platform, a second insulation platform, and a third insulation platform; the temperature of the first insulation platform is 300-450°C, the temperature of the second insulation platform is 450-650°C, and the temperature of the third insulation platform is 950-990°C; B. When condition A is met, the heating rate of the first insulation platform is 4-6°C / min, and the heating rates of the second insulation platform and the third insulation platform are independently 1-3°C / min; C. When condition A is met, the insulation time of the first insulation platform is 4-6 hours, the insulation time of the second insulation platform is 6-8 hours, and the insulation time of the third insulation platform is 10-12 hours.
[0014] In some embodiments, at least one of the following conditions is met: A. The secondary sintering temperature is 400-600°C; B. The heating rate of the secondary sintering is 3-5°C / min; C. The constant temperature time of the secondary sintering is 5-10h; D. The temperature of the three sintering processes is 400-500°C, the constant temperature time is 4-6h, and the heating rate is 3-5°C / min.
[0015] In some embodiments, at least one of the following conditions is met: A. The sintering equipment includes one of the following: muffle furnace, tube furnace, box furnace, bell furnace; B. The oxygen-containing atmosphere includes one of pure oxygen, compressed air, purified gas, and ordinary air; C. Ni x Mn y The internal porosity of (OH)2 is ≥25%.
[0016] The present application also provides a lithium-ion battery comprising the above-mentioned modified lithium-rich manganese-based positive electrode material.
[0017] Compared with the prior art, the advantages of this application include: The modified lithium-rich manganese-based positive electrode material provided in the present application performs multi-element point doping on the base material to enhance the structural stability of the polycrystalline material, inhibit the migration of transition metal ions and interlayer dislocations, improve the internal lattice strength, and manufacture a stable base material core; the heterostructure layer can greatly improve the oxidation resistance of the material surface under high voltage, increase the stability of the base material surface, and its in situ generated three-dimensional ion channels can improve the material rate performance; the coating layer can effectively reduce the side reactions at the solid-liquid interface, improve the dissolution of surface metal ions, and improve the material cycle performance; in short, the present application mainly combines the above-mentioned three means of specific element doping, heterostructure surface layer modification design and surface coating to effectively and comprehensively modify the internal structure, surface layer and outer surface of the material, which can improve the capacity performance, rate performance and cycle performance of the lithium-rich manganese-based positive electrode material.
[0018] The preparation method of the modified lithium-rich manganese-based positive electrode material provided in the present application first utilizes a multi-stage heat preservation stage of a single sintering process to perform multi-point doping of a specific multi-element on the base material to improve the performance; then, a high-temperature treatment is performed at 400-600°C in an inert atmosphere to oxidize part of the oxygen on the surface of the material, forming a certain amount of oxygen vacancies and reducing the migration energy of the Mn ions, thereby promoting the migration of Mn to the oxygen vacancies and in-situ formation of spinel-phase lithium manganate Li4Mn5O 12The method comprises the following steps: forming a heterogeneous structure layer; then coating with a D-containing compound to form a coating layer; by combining the above three methods of specific element doping, heterogeneous structure surface layer modification design and surface coating, the internal structure, surface layer and outer surface of the material are effectively modified in a comprehensive manner, exerting a synergistic effect, and obtaining a modified lithium-rich manganese-based positive electrode material with comprehensively improved capacity rate cycle performance.
[0019] If a single one-burning doping is used, the internal structural strength of the crystal will increase to a certain extent, but the surface oxygen partial pressure will be too large and the oxygen activity will not be controlled, which will cause the material to be over-oxidized in a high-voltage environment, and the surface metal ions will continue to migrate inward and cause structural decomposition. In addition, the surface is not effectively coated to isolate the solid-liquid interface, which will also deteriorate the material's cycle performance. In short, this application starts from the three levels of body-surface-surface, and after comprehensive modification, the electrochemical properties of the material such as first effect, cycle, and voltage attenuation can be greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0021] Figure 1 Schematic diagram of the process for preparing the modified lithium-rich manganese-based positive electrode material of the present application; Figure 2 This is an SEM image of the modified lithium-rich manganese-based positive electrode material of Example 1; Figure 3 This is the XRD diffraction pattern of the modified lithium-rich manganese-based positive electrode material of Example 1; Figure 4 This is the XRD diffraction pattern of the modified lithium-rich manganese-based positive electrode material of Comparative Example 1; Figure 5 Graph showing the cycle performance of the modified lithium-rich manganese-based positive electrode materials of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0022] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variations thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0023] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed alone. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0024] In these examples, parts and percentages are by mass unless otherwise indicated.
[0025] "Parts by mass" refers to the basic unit of measurement used to express the mass ratio of multiple components. One part can represent any unit of mass, such as 1g or 2.689g. For example, if we say that the parts by mass of component A are a parts and the parts by mass of component B are b parts, this means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, we could say that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number representing a multiplication factor). It's important to note that, unlike parts by mass, the sum of the parts by mass of all components is not limited to 100 parts.
[0026] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0027] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of the technical features being referred to. Thus, a feature identified as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "plurality" means two or more, unless otherwise specifically defined.
[0028] The present application provides a modified lithium-rich manganese-based positive electrode material, comprising: a base material, a heterogeneous structure layer and a coating layer; The matrix material is a polycrystalline or single-crystal solid solution particle, and its chemical formula is Li w Ni x Mn y M a N b L c O w+1-r Q r, where 1.2≤w≤1.4, 0.25≤x≤0.40, 0.50≤y≤0.70, 0.0005≤a≤0.002, 0.0001≤b≤0.002, 0.0001≤c≤0.004, x+y+a+b+c=1, 0≤r≤0.002; Wherein, M and L are independently selected from at least one of Nb, Ti, Mg, Co, W, La, Te and Ta, preferably, M is selected from at least one of Nb, Ti and Mg, L is selected from at least one of Co, W and La, more preferably, M and L are Nb and Co respectively; N is selected from at least one of Zn, Na, Cr, Zr and K, preferably, N is selected from at least one of Zn, Na and K, more preferably, N is Zn; Q is selected from at least one of F, Cl, S, B and P, preferably, Q is selected from at least one of F, Cl, S and P; preferably, r is 0.
[0029] The heterostructure layer contains spinel phase lithium manganate Li4Mn5O 12 ; The coating layer is a D-containing compound, which includes one or more of fluorides, oxides, sulfates, nitrates or phosphates of Al and / or La, and preferably includes one or more of fluorides, oxides, sulfates, nitrates or phosphates of Al.
[0030] The modified lithium-rich manganese-based positive electrode material provided in the present application performs multi-element point doping on the base material to enhance the structural stability of the polycrystalline material, inhibit the migration of transition metal ions and interlayer dislocations, improve the internal lattice strength, and manufacture a stable base material core; the heterostructure layer can greatly enhance the oxidation resistance of the material surface under high voltage, increase the stability of the base material surface, and its in situ generated three-dimensional ion channels can improve the material rate performance; the coating layer can effectively reduce the side reactions at the solid-liquid interface, improve the dissolution of surface metal ions, and improve the material cycle performance; in short, the present application mainly combines the above-mentioned three means of specific element doping, heterostructure surface layer modification design and surface coating to effectively and comprehensively modify the internal structure, surface layer and outer surface of the material, which can improve the capacity performance, rate performance and cycle performance of the lithium-rich manganese-based positive electrode material.
[0031] In some embodiments, M is preferably Nb, L is preferably Co, and N is preferably Zn.
[0032] The synergistic doping of Nb with multiple elements has two effects. First, it enhances the transition metal-oxygen bond energy by doping the layered phase transition metal sites, stabilizing the transition metal ions in the lattice and reducing their migration barriers. Second, excess Nb accumulates on the material surface and grain boundaries, forming fast ion conductors such as LiNbO3 on the surface, improving the material's conductivity. This grain boundary enrichment inhibits primary particle growth, allowing the primary particles to maintain good crystallinity at high temperatures without sacrificing capacity. Zn acts as a Li layer doper, targeting Li vacancies and blocking the migration path of transition metal elements into the Li layer. Co enters the Li2MnO3 phase and catalyzes oxygen activity. These multiple elements work synergistically to improve rate capability and discharge capacity.
[0033] If the Nb doping level is too low, it will not form many transition metal-oxygen bonds or large-area grain boundary enrichment, and it will not be able to effectively prevent harmful phase changes and structural degradation of the material. If the Nb doping level is too high, it will lead to the formation of inert metal impurities or enrichment on the material surface, reducing the electrochemical activity of the material and hindering the extraction and insertion of lithium ions. Similarly, if the Zn doping level is too low, it will not be able to prevent sufficient transition metal ions from migrating to the lithium layer. If the Zn doping level is too high, it will increase the degree of cation mixing in the Li layer and cause the structure to collapse too quickly. If the Co doping level is too low, a certain degree of O activation cannot be achieved. If the Co doping level is too high, too much O will be activated, accelerating the decay of the structure.
[0034] In some embodiments, the internal porosity of the modified lithium-rich manganese-based positive electrode material is ≥15%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value ≥15%, preferably 15% to 20%.
[0035] In some embodiments, the modified lithium-rich manganese-based positive electrode material has a secondary spherical morphology formed by the accumulation of primary particles, and the average length of the primary particles is 150-200 nm, for example, it can be 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any value between 150-200 nm.
[0036] In some embodiments, the average particle size D50 of the modified lithium-rich manganese-based positive electrode material is 3-10 μm, for example, it can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value between 3-10 μm.
[0037] This application also provides a method for preparing the modified lithium-rich manganese-based positive electrode material. Figure 1 ,include: S100: In an oxygen-containing atmosphere, Ni x Mn y(OH)2, a lithium source, a compound containing M, a compound containing N, and a compound containing L are mixed and sintered once to obtain a sintered product; S200: performing secondary sintering on the primary sintered product under an inert atmosphere to obtain a secondary sintered product having a heterogeneous structure layer; S300: The secondary calcined product is mixed with an additive and sintered three times to obtain a modified lithium-rich manganese-based positive electrode material with a coating layer.
[0038] The preparation method of the modified lithium-rich manganese-based positive electrode material provided in the present application first utilizes a multi-stage heat preservation stage of a single sintering to perform multi-point doping of a specific multi-element on the base material to improve the performance; then, the base material is subjected to a high-temperature treatment at 400-600°C in an inert atmosphere (such as a nitrogen atmosphere, an argon atmosphere, or a helium atmosphere), so that part of the oxygen on the surface of the material is oxidized to form a certain amount of oxygen vacancies, while at the same time reducing the migration energy of the Mn ions, promoting the migration of Mn to the oxygen vacancies, and in situ forming a spinel phase lithium manganate Li4Mn5O 12 The method comprises the following steps: forming a heterogeneous structure layer; then coating with a D-containing compound to form a coating layer; by combining the above three methods of specific element doping, heterogeneous structure surface layer modification design and surface coating, the internal structure, surface layer and outer surface of the material are effectively modified in a comprehensive manner, exerting a synergistic effect, and obtaining a modified lithium-rich manganese-based positive electrode material with comprehensively improved capacity rate cycle performance.
[0039] If a single one-burning doping is used, the internal structural strength of the crystal will increase to a certain extent, but the surface oxygen partial pressure will be too large and the oxygen activity will not be controlled, which will cause the material to be over-oxidized in a high-voltage environment, and the surface metal ions will continue to migrate inward and cause structural decomposition. In addition, the surface is not effectively coated to isolate the solid-liquid interface, which will also deteriorate the material's cycle performance. In short, this application starts from the three levels of body-surface-surface, and after comprehensive modification, the electrochemical properties of the material such as first effect, cycle, and voltage attenuation can be greatly improved.
[0040] In some embodiments, the Ni in step S100 x Mn y In (OH)2, 0.28≤x≤0.42, 0.58≤y≤0.72, x+y=1.
[0041] In some embodiments, the lithium source in step S100 includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, or lithium acetate.
[0042] In some embodiments, the Ni in step S100 x Mn y(OH)2: Lithium source: (Compound containing M + Compound containing N + Compound containing L) molar ratio is 0.997: (1.20 - 1.40): 0.003, for example, it can be 0.997: 1.20: 0.003, 0.997: 1.25: 0.003, 0.997: 1.30: 0.003, 0.997: 1.35: 0.003, 0.997: 1.40: 0.003 or any ratio between 0.997: (1.20 - 1.40): 0.003.
[0043] In some embodiments, the oxygen-containing atmosphere in step S100 includes one of pure oxygen, compressed air, purified gas, and ordinary air.
[0044] In some embodiments, Ni x Mn y The internal porosity of (OH)2 ≥ 25%.
[0045] In some embodiments, the primary sintering in step S100 includes a first heat preservation platform, a second heat preservation platform, and a third heat preservation platform; the temperature of the first heat preservation platform is 300 - 450 °C, for example, it can be 300 °C, 350 °C, 400 °C, 450 °C or any value between 300 - 450 °C, the temperature of the second heat preservation platform is 450 - 650 °C, for example, it can be 450 °C, 500 °C, 550 °C, 600 °C, 650 °C or any value between 450 - 650 °C, the temperature of the third heat preservation platform is 950 - 990 °C, for example, it can be 950 °C, 960 °C, 970 °C, 980 °C, 990 °C or any value between 950 - 990 °C.
[0046] The first heat preservation platform mainly promotes the full reaction of the precursor and the lithium salt, mainly generating intermediate transition phases Li w’ TM 1-w’ TM2O4 (0 < w’ < 1) and layered phase LiTMO2. At this time, the M element gradually diffuses into the layered transition metal site synchronously and randomly replaces the Ni / Mn atomic site; the second heat preservation platform corresponds to the transformation of the LiTMO2 phase to the Li2MnO3 phase, and the L element gradually embeds into the Li2MnO3 lattice, replacing part of the Mn atoms to generate Li2[Li 1 / 3 [MnL] 2 / 3 O3; both the first heat preservation platform and the second heat preservation platform will be accompanied by the random replacement of the Li site by the N element; the third heat preservation platform is high-temperature sintering, and the high temperature provides the driving force for ion diffusion to promote the doping of each element at the corresponding lattice positions to complete the corresponding amount.
[0047] In some embodiments, the heating rate of the first insulation platform in step S100 is 4~6°C / min, for example, it can be 4°C / min, 5°C / min, 6°C / min or any value between 4~6°C / min, and the heating rates of the second insulation platform and the third insulation platform are independently 1~3°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min or any value between 1~3°C / min.
[0048] In some embodiments, the insulation time of the first insulation platform in step S100 is 4-6 hours, for example, it can be 4 hours, 5 hours, 6 hours or any value between 4-6 hours, the insulation time of the second insulation platform is 6-8 hours, for example, it can be 6 hours, 7 hours, 8 hours or any value between 6-8 hours, and the insulation time of the third insulation platform is 10-12 hours, for example, it can be 10 hours, 11 hours, 12 hours or any value between 10-12 hours.
[0049] In some embodiments, the temperature of the secondary sintering in step S200 is 400-600°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, or any value between 400-600°C; the heating rate of the secondary sintering is 3-5°C / min, for example, 3°C / min, 4°C / min, 5°C / min, or any value between 3-5°C / min; the constant temperature time of the secondary sintering is 5-10h, for example, 5h, 6h, 7h, 8h, 9h, 10h, or any value between 5-10h. The thickness of the heterostructure layer can be appropriately controlled by the heat treatment temperature and time under an inert atmosphere and controlled to be around a few nanometers. Too thick will result in a longer Li ion diffusion path and reduced capacity, while too thin will have no obvious effect. The composition of the heterostructure layer can be detected by XRD diffraction pattern.
[0050] The primary sintered product is subjected to secondary sintering under an inert atmosphere, and a large number of oxygen vacancies are created using the inert atmosphere. These vacancies react with the surface metal elements to form a heterogeneous structure layer. This layer can greatly enhance the oxidation resistance of the material surface under high voltage, increase the stability of the substrate material surface, and its in-situ generated three-dimensional ion channels can improve the material rate performance.
[0051] In some embodiments, the sintering equipment includes one of a muffle furnace, a tube furnace, a box furnace, and a bell furnace.
[0052] In some embodiments, the additive in step S300 includes at least one of aluminum fluoride, aluminum oxide, aluminum sulfate, aluminum nitrate, aluminum phosphate, lithium aluminum titanium phosphate, lanthanum oxide, and lithium aluminum zirconate.
[0053] Preferably, the additive includes at least one of aluminum oxide, aluminum fluoride, aluminum phosphate, and lanthanum oxide; More preferably, the additive comprises aluminum fluoride.
[0054] More preferably, the additive is aluminum fluoride. The role of aluminum fluoride is to utilize the high stability of fluoride in the electrolyte to reduce excessive side reactions of the material at the solid-liquid contact interface, thereby improving the material's cycle stability, especially in lithium-rich high-voltage systems.
[0055] In some embodiments, the amount of the additive added in step S300 is 0.5%-1.5% of the mass of the di-sintered product, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any value between 0.5% and 1.5%.
[0056] Since step S300 is a dry coating method, a uniform coating layer cannot be achieved. Therefore, too little coating amount cannot form a sufficient island-shaped coating network on the material surface, while too much coating amount will increase the interface impedance and affect the discharge capacity.
[0057] In some embodiments, the temperature of the three sinterings in step S300 is 400-500°C, for example, it can be 400°C, 450°C, 500°C or any value between 400-500°C; the constant temperature time is 4-6h, for example, it can be 4h, 5h, 6h or any value between 4-6h, and the heating rate is 3-5°C / min, for example, it can be 3°C / min, 4°C / min, 5°C / min or any value between 3-5°C / min.
[0058] The present application also provides a lithium-ion battery comprising the above-mentioned modified lithium-rich manganese-based positive electrode material.
[0059] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, the conditions are carried out according to conventional conditions or manufacturer recommendations. The reagents or instruments used are not specified by the manufacturer and are conventional products that can be purchased commercially.
[0060] Example 1 This embodiment provides a modified lithium-rich manganese-based cathode material, which comprises a matrix material, a heterogeneous structure layer and a coating layer. The matrix material is a polycrystalline solid solution particle, and its chemical formula is Li w Ni x Mn y M a N b L c O w+1, where w=1.33, x=0.349, y=0.648, M element is Nb, N element is Zn, L element is Co, a=0.001, b=0.0005, c=0.0015.
[0061] This embodiment also provides a method for preparing a modified lithium-rich manganese-based positive electrode material, comprising the following steps: (1) In an oxygen-containing environment, Ni 0.35 Mn 0.65 (OH)2 precursor, lithium carbonate, niobium oxide, cobalt oxyhydroxide, and zinc oxide are mixed evenly. x Mn y The molar ratio of (OH)2: lithium carbonate: (niobium oxide + cobalt oxyhydroxide + zinc oxide) was 0.997:1.33:0.003, and a primary sintering process was performed in a muffle furnace. The primary sintering process consisted of three holding stages: the first at 350°C, with a heating rate of 5°C / min for 5 hours; the second at 550°C, with a heating rate of 2°C / min for 5 hours; and the third at 965°C, with a heating rate of 2°C / min for 7 hours. Ordinary air was used as the oxygen source during the sintering process, resulting in a Nb / Co / Zn-doped primary sintered product.
[0062] (2) The obtained first-fired product was subjected to a second sintering treatment in a nitrogen atmosphere, after which the temperature was raised to 500°C at 4°C / min, kept at that temperature for 8 hours, and then cooled to room temperature to obtain a second-fired product having a heterogeneous structure layer.
[0063] (3) The obtained di-sintered product was mixed evenly with the additive aluminum fluoride, with the amount of the additive added being 1% of the mass of the di-sintered product. The product was sintered for the third time, and the temperature was raised to 450°C at 4°C / min, kept at that temperature for 5 hours, and then cooled to room temperature to obtain a lithium-rich manganese-based positive electrode material containing a coating layer.
[0064] The SEM image of the modified lithium-rich manganese-based positive electrode material prepared in Example 1 is as follows: Figure 2 As shown, the average particle size D50 is 6.5 μm and the internal porosity is 18%; the XRD diffraction pattern of the modified lithium-rich manganese-based positive electrode material is shown in Figure 3 , showing that the heterostructure layer contains spinel phase lithium manganate Li4Mn5O 12 The material has a secondary spherical morphology formed by the accumulation of primary particles, and the average length of the primary particles is 170nm.
[0065] Example 2 The difference between Example 2 and Example 1 is that in the preparation method of the modified lithium-rich manganese-based positive electrode material, the first insulation platform temperature of step (1) is 300°C, the second insulation platform temperature is 450°C, and the third insulation platform temperature is 950°C. The remaining steps are the same as in Example 1.
[0066] Example 3 The difference between Example 3 and Example 1 is that in the preparation method of the modified lithium-rich manganese-based positive electrode material, the first insulation platform temperature of step (1) is 450°C, the second insulation platform temperature is 650°C, and the third insulation platform temperature is 990°C. The remaining steps are the same as in Example 1.
[0067] Example 4 The difference between Example 4 and Example 1 is that the Ni 0.35 Mn 0.65 The molar ratio of (OH)2 precursor: lithium carbonate: (niobium oxide + cobalt oxyhydroxide + zinc oxide) is 0.997:1.20:0.003, and the remaining steps are the same as in Example 1.
[0068] Example 5 The difference between Example 5 and Example 1 is that the Ni in step (1) of the preparation method of modified lithium-rich manganese-based positive electrode material is 0.35 Mn 0.65 The molar ratio of (OH)2 precursor: lithium carbonate: (niobium oxide + cobalt oxyhydroxide + zinc oxide) is 0.997:1.40:0.003, and the remaining steps are the same as in Example 1.
[0069] Example 6 The difference between Example 6 and Example 1 is that M is Ti, N is Zn, and L is W. The remaining steps are the same as those in Example 1.
[0070] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that there is no step (2), and the remaining steps are the same as those in Example 1.
[0071] The XRD diffraction pattern of the modified lithium-rich manganese-based positive electrode material of Comparative Example 1 is shown in Figure 4 , showing no spinel phase lithium manganate Li4Mn5O 12 .
[0072] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in the preparation method of the modified lithium-rich manganese-based positive electrode material, the first insulation platform temperature of step (1) is 260°C, the second insulation platform temperature is 400°C, and the third insulation platform temperature is 900°C. The remaining steps are the same as in Example 1.
[0073] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in the preparation method of the modified lithium-rich manganese-based positive electrode material, the first insulation platform temperature of step (1) is 500°C, the second insulation platform temperature is 700°C, and the third insulation platform temperature is 1100°C. The remaining steps are the same as in Example 1.
[0074] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in the preparation method of the modified lithium-rich manganese-based positive electrode material, step (1) does not have the first insulation platform, the temperature of the second insulation platform is 550°C, the temperature of the third insulation platform is 965°C, and the remaining steps are the same as in Example 1.
[0075] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in step (1) of the preparation method of the modified lithium-rich manganese-based positive electrode material, cobalt oxyhydroxide is not added for mixing, and the remaining steps are the same as those in Example 1.
[0076] Test example: Electrochemical performance test The positive electrode materials prepared in the Examples and Comparative Examples were mixed with PVDF and NMP in a ratio of 90:5:5 to prepare a positive electrode slurry. This slurry was then coated onto aluminum foil, dried, and then punched and sheared to produce positive electrode sheets. Button cells were assembled in a glove box. The positive electrode sheets were combined with lithium sheets, separators, and electrolyte to form a button cell. The assembled button cell was placed in the mold of a hydraulic sealing machine, locked, pressurized, and then unlocked to remove the sealed button cell. The separator was Celgard polypropylene film, and the electrolyte was purchased from Guangzhou Tianci.
[0077] Testing was performed using a Lanhe (model: CT3002A) battery test cabinet over a voltage range of 2.5V to 4.52V. Specifically, the batteries were charged at a constant current of 0.1C to 4.52V, charged at a constant voltage of 0.02C, and discharged at 0.1C to 2.5V. This was considered the first activation cycle. Next, the batteries were charged at a constant current of 0.33C to 4.52V, charged at a constant voltage of 0.02C, and discharged at 1C to 2.5V. The discharge capacity after the second cycle was recorded as the 0.33C discharge capacity (mAh / g). Finally, the batteries were charged at a constant current of 1C to 4.52V, charged at a constant voltage of 0.02C, and discharged at 1C to 2.5V. The discharge capacity after the second cycle was recorded as the 1C discharge capacity (mAh / g). This 1C charge-discharge cycle was repeated until the 80th cycle. The discharge capacity at the 80th cycle was recorded, and the 1C 80-cycle retention rate (%) was calculated.
[0078] The capacity retention rates of the modified lithium-rich manganese-based positive electrode materials of Example 1 and Comparative Example 1 are as follows: Figure 5 The electrochemical performance test data of the positive electrode materials of various embodiments and comparative examples are shown in Table 1.
[0079] Table 1 Electrochemical performance test data of the positive electrode materials of various embodiments and comparative examples
[0080] Comparative Example 1 lacks a heterogeneous structure layer, resulting in poor surface structure antioxidant capacity and severe transition metal ion dissolution and rearrangement, leading to poor cycle performance. Comparative Example 2 uses an excessively low sintering temperature, resulting in a low degree of material crystallization, low lithium salt diffusion, phase reaction, and metal ion migration, and high internal resistance, leading to lower rate capacity and cycle performance. Comparative Example 3 uses an excessively high sintering temperature, resulting in excessively large primary particles, an excessively long lithium ion migration path, and reduced ionic conductivity. Consequently, the capacity is lower than that of Comparative Example 2 or Example 1, and the cycle performance also deteriorates. Comparative Example 4 lacks a first insulation platform, resulting in insufficient decomposition of the lithium salt and precursor, a relatively low proportion of layered phase and intermediate transition phase formation, and a reduced site occupation by the doped metal ions in the subsequent high-temperature solid-phase reaction, which reduces the effect on crystal structure stability and reduces cycle performance. Comparative Example 5 lacks Co doping, which reduces the release of lithium at the 3a / 3b sites, resulting in poor capacity (rate capacity), but at the same time, a certain degree of improvement in cycle stability.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
[0082] Furthermore, those skilled in the art will appreciate that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and to form distinct embodiments. For example, in the claims above, any of the claimed embodiments may be used in any combination. The information disclosed in this background section is intended solely to enhance understanding of the overall background of this application and should not be construed as an admission or any implication that such information constitutes prior art known to those skilled in the art.
Claims
1. A modified lithium-rich manganese-based positive electrode material, characterized in that: include: Base material, heterogeneous structure layer and cladding layer; The matrix material is a polycrystalline or single-crystal solid solution particle, and its chemical formula is Li w Ni x Mn y M a N b L c O w+1-r Q r , where 1.2≤w≤1.4, 0.25≤x≤0.40, 0.50≤y≤0.70, 0.0005≤a≤0.002, 0.0001≤b≤0.002, 0.0001≤c≤0.004, x+y+a+b+c=1, 0≤r≤0.002; wherein M and L are independently selected from at least one of Nb, Ti, Mg, Co, W, La, Te and Ta; N is selected from at least one of Zn, Na, Cr, Zr, and K; Q is selected from at least one of F, Cl, S, B, and P; The heterostructure layer comprises spinel phase lithium manganate Li4Mn5O 12 ; The coating layer is a D-containing compound, and the D-containing compound includes one or more of fluorides, oxides, sulfates, nitrates or phosphates of Al and / or La.
2. The modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that The internal porosity of the modified lithium-rich manganese-based positive electrode material is ≥15%.
3. The modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that The modified lithium-rich manganese-based positive electrode material has a secondary spherical morphology formed by accumulation of primary particles, and the average length of the primary particles is 150-200 nm.
4. The modified lithium-rich manganese-based cathode material according to claim 1, characterized in that The average particle size D50 of the modified lithium-rich manganese-based positive electrode material is 3-10 μm.
5. A method for preparing a modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: include: In an oxygen-containing atmosphere, Ni x Mn y (OH)2, a lithium source, a compound containing M, a compound containing N, and a compound containing L are mixed and sintered once to obtain a sintered product; The primary calcined product is subjected to secondary calcination under an inert atmosphere to obtain a secondary calcined product having a heterogeneous structure layer; The double-sintered product is mixed with an additive and sintered three times to obtain a modified lithium-rich manganese-based positive electrode material with a coating layer.
6. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: At least one of the following conditions is met: A. The Ni x Mn y In (OH)2, 0.28≤x≤0.42, 0.58≤y≤0.72, x+y=1; B. the lithium source comprises at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate or lithium acetate; C. Ni x Mn y The molar ratio of (OH)2: the lithium source: (the compound containing M + the compound containing N + the compound containing L) is 0.997: (1.20-1.40): 0.003; D. The additive comprises at least one of aluminum fluoride, aluminum oxide, aluminum sulfate, aluminum nitrate, aluminum phosphate, lithium aluminum titanium phosphate, lanthanum oxide, and lithium aluminum zirconate; E. The amount of the additive added is 0.5%-1.5% of the mass of the di-sintered product.
7. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: At least one of the following conditions is met: A. The primary sintering includes a first insulation platform, a second insulation platform, and a third insulation platform; the temperature of the first insulation platform is 300-450°C, the temperature of the second insulation platform is 450-650°C, and the temperature of the third insulation platform is 950-990°C; B. When condition A is met, the heating rate of the first insulation platform is 4-6°C / min, and the heating rates of the second insulation platform and the third insulation platform are independently 1-3°C / min; C. When condition A is met, the insulation time of the first insulation platform is 4-6 hours, the insulation time of the second insulation platform is 6-8 hours, and the insulation time of the third insulation platform is 10-12 hours.
8. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: At least one of the following conditions is met: A. The secondary sintering temperature is 400-600°C; B. The heating rate of the secondary sintering is 3-5°C / min; C. The constant temperature time of the secondary sintering is 5-10h; D. The temperature of the three sintering processes is 400-500°C, the constant temperature time is 4-6h, and the heating rate is 3-5°C / min.
9. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 8, characterized in that: At least one of the following conditions is met: A. The sintering equipment includes one of the following: muffle furnace, tube furnace, box furnace, bell furnace; B. The oxygen-containing atmosphere includes one of pure oxygen, compressed air, purified gas, and ordinary air; C. Ni x Mn y The internal porosity of (OH)2 is ≥25%.
10. A lithium ion battery, characterized in that: The modified lithium-rich manganese-based positive electrode material comprises the modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Linkage modified lithium-rich manganese-based positive electrode material and preparation method thereof
CN111509224A
Spinel / layered heterostructure modified cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof
CN114671471A
Positive electrode for lithium secondary battery and lithium secondary battery comprising same
CN115050924A
Lithium ion battery positive electrode material, preparation method thereof and lithium ion battery
CN116632240A
Lithium-rich manganese-based positive electrode material with multi-layer composite structure and preparation method of lithium-rich manganese-based positive electrode material
CN117199300A
Cited By
Modified lithium-rich manganese-based positive electrode material, preparation method thereof and battery
CN121601630A
Lithium-rich manganese-based positive electrode material with surface induced phase change and preparation method of lithium-rich manganese-based positive electrode material
CN121726399A
Preparation method and application of Al / W / Se ternary synergistic modified lithium-rich manganese-based positive electrode material
CN121839526A